PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS, PROFITABILITAS, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Tammy Rizkillah, Sudiyanti; Nurbaiti, Annisa (Yayasan Akrab Pekanbaru, 2018)
A going concern audit opinion is an opinion given by the auditor if the company can not maintain the survival of an entity. A going concern audit opinion can be used as an early warning for users of financial statements to avoid mistakes in decision making. Issuance of going concern audit opinion will affect the loss of public confidence in corporate image and company management. This will affect the sustainability of the business going forward. This study aims to determine the variable size of the company, financial distress, profitability, and previous year audit opinion. The object of research used is mining sector companies period 2012-2016. The sample selection technique used purposive sampling and obtained sample of 135 research samples from 27 companies. Data analysis model used in this research using panel data regression analysis technique using SPSS 20 software. The result of this research indicate that firm size variable have a significant positive effect on giving of going concern audit opinion, profitability have a significant negative effect to giving going concern audit opinion, while financial distress and previous year audit opinion have no significant effect on giving going concern audit opinion.. Key word: Company size, financial distress, profitability, previous year audit opinion and audit opinion going concern.